Pengaruh Kualitas Produk Dan Label Halal Terhadap Keputusan Pembelian Dengan Kepercayaan Sebagai Variabel Mediasi: Studi Kasus pada Follower Instagram Scarlett - Manurung, Carnelius Ricardo; Rosida, Rosida; Sarwoto, Sarwoto (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
The aim of this study was to examine how the impact of product quality and the presence of a halal label affect consumer purchasing choices, with trust playing a mediating role. The study focused on Scarlett's Instagram followers. The study explored both direct and indirect effects. This research falls under the category of explanatory research, aiming to elucidate causal relationships between variables through hypothesis testing. The study employed a quantitative approach utilizing SmartPLS (Partial Least Square) software version 3.0. Two sub-models were utilized: the measurement model (outer model) and the structural model (inner model). The sampling method employed was accidental, with 97 respondents chosen using the Cochran formula. The direct impact analysis revealed that product quality significantly influenced purchasing decisions, with a value of 2.246 and a significant value of 0.025. However, the presence of a halal label did not significantly affect purchasing decisions, registering a value of 0.317 and a significant value of 0.751. Product quality significantly influenced trust, with a value of 7.556 and a significant value of 0.000, while the halal label did not significantly affect trust, with a value of 1.934 and a significant value of 0.054. Trust significantly influenced purchasing decisions, with a value of 20.906 and a significant value of 0.000. Regarding the indirect effects, trust was found to mediate the relationship between product quality and purchasing decisions, with a value of 6.618 and a significant value of 0.000. However, trust was not found to mediate the relationship between halal labels and purchasing decisions, with a value of 1.943 and a significant value of 0.053.